Teologi Islam dan Fanatisme Perilaku Sosial Beragama - Zulkarnain Zulkarnain (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2021)
Fanatic is a term used to refer to a belief or a view of something positive or negative, which view does not have a theoretical backing or a foundation of reality, but is profoundly embraced so that it is difficult to straighten or change. The root problem of this discussion is the fanatical attitude of religious people, and the low level of understanding of religion, because they only see an event from a narrow perspective without seeing the consequences of what is caused. The weak self-confidence of adherents of religion to the teachings of religion that have been adopted since he was in a family environment, so easily influenced by the factors of fanaticism. As a believer in an individual religion must have a firm belief in the religion he has adopted and has been deemed correct according to the Act of government. The aim of the author to raise this phenomenon is to describe the mindset of an individual who is fanaticism-oriented, would this attitude undermine social interaction, or even fanaticism is a phenomenon that is mushrooming in the future.